Imprensa e Revolução de 1930: as constelações simbólicas na raiz noticiosa de A União e do Jornal do Commercio - Silva, Nayane Maria Rodrigues da (2019)
This research frees conservative intellect and suspicious impressions about one of the most emblematic episodes of Brazil’s political history - The Brazilian Revolution of 1930. To exhaust the possibilities of theoretical-methodological approximation that embrace journalism, imaginary, and historiography, aimed to identify the multiplicity of meanings in the headlines of a couple of newspapers, such as A União (from Paraíba) and Jornal do Commercio (from Pernambuco) during the Brazilian Revolution of 1930, it was stablished a functional and original symbolic interpretation about the episode of proclamation of Free Territory of Princesa. Subjective values and sensitive attributes were identified from newsworthiness criteria that detected the strong evidence of new values conflict, prominence, government, tragedy/drama, and surprise. Isotopic classification and image regimes from Gilbert Durand noted the prevalence of symbolic constellations ruled by daytime regime of image. What remained was anguish, torment, distress, agony, and disquiet on the headlines. The heroic postural reflection stiffed the journalistic agenda with headlines that caused even more division, separation, superiority, justice, and power. Mythcriticism and mythanalysis, from mythdology, manifested images on universes mythical heroic and dramatic, which predominance of mythems demonstrating distinction, strength, challenge, resistance, aggressiveness, and threat reaffirmed the symbolic force from heroic mythical universe, which highlights the existence of perceptive images on periodicals, through real symbolic constellations. They are values, attributes, mythems, myths, and archetypes which remain in full battle, by the resonance that they have and resistance to action of time and to the spiral of silence. More than a study, an alert to researchers, journalists, historians, mythologists, and communicologists about the emotional sense of these mental images which, demonstrably, find themselves in conditions to influence imaginations and cause the weighted psychosocial imbalance by the mythodology of Gilbert Durand, about the singularities of The Brazilian Revolution of 1930.